Pattern Recognition of Phytoconstituents and Bioactivities of Date Pit Extracts from Different Cultivars Grown in the Qassim Area - Elham Amin; Enas I. A. Mohamed; Amani Salem Alenezi; Maemonh Ali Aldwesh; Mohamed Sebak; Ibrahim A. Naguib; Sarah I. Bukhari; Khulud Bukhari; Mohamed A. Zaki; Naglaa Afifi (Separations, 2023)
A huge number of date varieties grow annually throughout the world. The genetic variation between different date varieties is reflected in their variable sensory characters and phytochemical contents. Date pits are considered a waste product of the date industry, despite their rich metabolic content. The present study attempts to generate visual clustering to clarify the diversity among fourteen date cultivars growing in the Qassim region, according to the phytochemical contents and biological potentials of their pits. The results indicated a wide variation in the total phenolic content (11.4–29.7 mg GAE/g), flavonoids content (21.9–37.1 mg RE/g), proanthocyanidine content (12.0–207.0 mg CE/g), and antioxidant potential (10.3–25.5 mg AEAC/g) among the tested cultivars. Screening the antimicrobial activity of extracts from the 14 tested cultivars indicated different activities against Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, Salmonella enterica, and Candida albicans. Multivariate analysis of phytochemical content and biological activity, using different analytical models, allowed the classification of the 14 cultivars into four classes, Class-1: Barhi, Safawi, and Sukkari; Class-2: Khodry and Nabtat Ali; Class-3: Ruthana, Segae, Shaqra, and Sheishee; and Class-4: Hulwa Aljouf, Mabroom, Meneifi, Rushodia, and Wannana. These findings provide a scientific basis for the classification of date pits which facilitates the future selection of promising candidates for more phytochemical and biological exploration.